Hydroxyurea therapy for children with sickle cell anemia: A systematic review and meta-analysis - Khansa, Firyal; Ghifari, Muhammad H.; Daffa, Muhammad B.; Nasywa, Fiola; Enitan, Seyi S.; Eleojo , Itodo G.; Ali, Mazen EI. (Narra Sains Indonesia, 2024)
Sickle cell anemia (SCA) is a major global health issue, particularly among pediatric population, influenced by factors such as malaria susceptibility and genetic distribution. On the other hand, hydroxyurea therapy has been a well-established and accepted treatment for SCA, with over 25 years of clinical experience. It has been proven to be safe and effective in preventing vaso-occlusive events and chronic organ damage. The aim of this study was to assess the efficacy of hydroxyurea in alleviating pediatric SCA. This study was comprised of a systematic literature search and meta-analysis in accordance with the PRISMA and the Cochrane Handbook guidelines. A systematic search was performed on PubMed, Cochrane, and ScienceDirect databases for relevant literature published as of January 2024. Placebo-controlled clinical trials reporting the efficacy of hydroxyurea in managing SCA among pediatric patients were included in the systematic review. The eligible studies were further assessed for its reporting quality using Risk of Bias 2.0. Pooled analysis was carried out using a random effect model, where the effect size was calculated based on the mean difference (MD) and 95% confidence interval (95%CI). Three randomized clinical trials comprised of 423 participants were included in the studies. Among patients receiving hydroxyurea, significant improvement was observed in fetal hemoglobin (HbF) with MD of 9.45% (95%CI: 2.15–16.75), but not in mean corpuscular volume (MCV) (MD=8.77 fL (95%CI: -28.85–46.39). Hydroxyurea also significantly reduced white blood cell (WBC) (MD=-4.21 cells/mm3; 95%CI: -5.68–-2.93), absolute neutrophil count (ANC) (MD=-1.43 cells/mm3; 95%CI: -2.11–-0.74), absolute reticulocyte count (ARC) (MD=-141.85 cells/mm3; 95%CI; -172.77–-110.94), and platelet count (MD=-74.92 cells/mm3; 95%CI: -117.05–-32.78). In conclusion, hydroxyurea is efficacious in treating pediatric SCA, as observed in the HbF, WBC, ANC, ARC, and platelet count.